Mxene / CNT / metal oxide aerogel packaging and reinforcing material and preparation method and application thereof
By using Mxene/CNT/metal oxide aerogel packaging materials in the radiation-resistant packaging reinforcement materials of electronic devices, combined with core-shell structure functional fillers and PVA crosslinking agents, and using freeze-drying technology, the problems of limited loading of functional fillers and agglomeration in existing materials affecting shielding performance are solved, and efficient and lightweight radiation-resistant packaging reinforcement effect is achieved.
Patent Information
- Application Number
- CN202411757379.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-03
AI Technical Summary
Existing radiation-resistant packaging reinforcement materials for electronic devices face problems such as limited loading of functional fillers and agglomeration affecting shielding performance when improving performance.
The Mxene/CNT/metal oxide aerogel packaging reinforcement material is adopted. The functional filler is designed as Bi2O3@Gd2O3 powder or BixGd2-xO3 powder in core-shell structure, and PVA is used as a crosslinker, combined with freeze-drying technology to achieve high load and good dispersion of the functional filler.
The high load capacity of functional fillers (up to 90%) is achieved, which avoids agglomeration, significantly improves the shielding performance of radiation-resistant packaging reinforcement materials, and is lightweight and efficient.
Smart Images

Figure CN119662206A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a Mxene / CNT / metal oxide aerogel packaging reinforcement material and a preparation method and application thereof, belonging to the technical field of electronic device radiation-resistant packaging reinforcement material and preparation thereof. Background Art
[0002] With the rapid development of nuclear industry, radiation medicine and aerospace technology, the probability of exposure to nuclear radiation in these fields is increasing. Therefore, electronic equipment placed in these irradiation scenes for a long time is also exposed to different types of radiation. Long-term radiation accumulation will cause damage to electronic devices and equipment, seriously affecting the normal operation of the equipment. Therefore, it is necessary to strengthen the radiation resistance of electronic devices in radiation environments. The passive packaging and reinforcement of electronic devices using packaging materials is simple, economical and efficient, so this method is more suitable for strengthening the radiation resistance of electronic devices.
[0003] The core of the radiation-resistant packaging reinforcement of electronic devices is to develop radiation-resistant packaging materials with excellent shielding performance. At present, metal skins or polymer-based composite materials are mainly used for radiation-resistant packaging of devices. However, the metal skin has a large mass, and the shielding ability of the metal skin is single and limited, so its application is severely limited in some fields with lightweight requirements. Compared with metal skin materials, polymer-based composite materials have the characteristics of light weight, and can be shielded for single or multiple types of rays by adjusting the type of functional fillers, and different types of polymer matrices can achieve different effects, showing great potential for the preparation of rigid or flexible packaging materials. However, if polymer-based composite materials are used as radiation-resistant packaging reinforcement materials to achieve better performance, it is necessary to increase their thickness or filler ratio of functional fillers. For some nano-reinforcements (such as nano-gadolinium oxide, oxide bait, etc.), the maximum filling amount in the polymer matrix can usually only reach 50% to 60%, so the improvement of their performance is limited. In addition, nanopowders are prone to agglomeration in the polymer matrix, which affects the shielding performance. Therefore, based on the above-mentioned problems of existing materials, it is necessary to develop a new radiation-resistant packaging reinforcement material for electronic devices.
[0004] Aerogels are low-density nanoporous solids with a fine open-pore structure and thus low density (0.003-0.15 kg / m 3 ), high porosity and large surface area (500-1000m 2 / g) makes them unique in many ways, providing possibilities for a large number of applications, some of which have already been commercialized. For the demand for radiation-resistant packaging reinforcement materials, the low density makes them have great potential in the selection of lightweight materials, and the high porosity and large surface area enable them to provide more loading sites for radiation-resistant functional particles, thereby maximizing the loading ratio of functional fillers. Moreover, the loose and porous structure of aerogels allows their density to be appropriately adjusted by compression, so that performance regulation can be achieved. Therefore, based on the above-mentioned advantages of aerogels, radiation-resistant packaging reinforcement materials based on aerogels show great application potential. Summary of the invention
[0005] In view of the above problems existing in the existing radiation-resistant packaging and reinforcement materials for electronic devices, the present invention provides a Mxene / CNT / metal oxide aerogel packaging and reinforcement material and a preparation method and application thereof.
[0006] The technical solution of the present invention:
[0007] One of the purposes of the present invention is to provide a method for preparing a MXene / CNT / metal oxide aerogel encapsulation reinforcement material, characterized in that after a MXene dispersion and a carbon nanotube dispersion are uniformly mixed, PVA is added, and after continuing to stir and fully mix, a functional filler is added, and continued to stir uniformly to obtain a slurry; then the slurry is placed in a mold, and a freezing technology is used for drying to obtain a MXene / CNT / metal oxide aerogel encapsulation material;
[0008] Among them, the functional filler is Bi2O3@Gd2O3 powder or Bi x G 2-x O3 powder.
[0009] It is further defined that the MAX phase of the MXene dispersion is Ti3AlC2, Ti2AlC, Ta4AlC3, Ta2AlC, Nb2AlC or Nb4AlC3, with a concentration of 5 to 15 mg / mL; and the concentration of the carbon nanotube dispersion is 5 to 15 mg / mL.
[0010] It is further defined that the mass ratio of Mxene to carbon nanotubes in the slurry is 3-6:1; the ratio of the mass of PVA to the total mass of Mxene and carbon nanotubes is 1-3:1; and the mass of the functional material is 1-90% of the total mass of Mxene and carbon nanotubes.
[0011] It is further defined that after adding PVA, stirring is performed at a rotation speed of 300 to 800 rpm for 5 to 30 minutes.
[0012] It is further defined that after adding the functional filler, stirring is performed at a rotation speed of 300 to 800 rpm for 0.5 to 2 hours.
[0013] It is further defined that the freezing technology is directional freeze-drying technology or liquid nitrogen freezing technology.
[0014] It is further defined that the preparation method of the core-shell structured Bi2O3@Gd2O3 powder comprises:
[0015] (1) Bi(NO3)3·5H2O, a precipitant, CTAB and water are mixed and reacted in a water bath at 90°C for 1 hour. The obtained precipitate is washed with deionized water, dried, and then placed in a tube furnace in an air atmosphere at 300-600°C for heat treatment for 1-2 hours. The powder is collected for later use;
[0016] (2) The powder obtained in step (1), Gd(NO3)3·6H2O and ethylene glycol are mixed, stirred at 180°C for 1-1.5 h, naturally cooled to room temperature and rinsed, and the powder obtained after drying is heat treated at 600°C for 1-2 h to obtain Bi2O3@Gd2O3 powder with a core-shell structure.
[0017] It is further defined that the mass ratio of Bi(NO3)3·5H2O and Gd(NO3)3·6H2O is (0-1):1.
[0018] In a further embodiment, the precipitating agent is urea or ammonia.
[0019] Further limit, Bi x G 2-x The preparation method of O3 powder is as follows: using glycine as fuel, Gd2O3 and Bi2O3 are dissolved in nitric acid to obtain a slurry, and then the slurry is dehydrated into a gel, and the temperature is raised to 250°C, and the gel is spontaneously combusted to obtain a combustion powder; then the combustion powder is calcined at 600°C for 1-3h to obtain Bi x G 2-x O3 powder.
[0020] It is further defined that the oxidant to fuel (O / F) ratio during the combustion process is 1:1.5.
[0021] It is further defined that the method for preparing the MXene dispersion comprises:
[0022] (a) Etching: The MAX phase is etched by hydrofluoric acid etching, HCl+LiF etching, NaOH autoclave etching or Lewis etching to obtain a two-dimensional layered structure MXene material;
[0023] (b) Stripping: The two-dimensional layered structure MXene material obtained in step (1) is subjected to ultrasonic and centrifugal treatment, the upper liquid of the centrifugation is collected, the precipitate is repeatedly subjected to the above ultrasonic and centrifugal treatment, and the upper liquid is combined to obtain a MXene dispersion.
[0024] It is further defined that the MAX phase in (a) is Ti3AlC2, Ti2AlC, Ta4AlC3, Ta2AlC, Nb2AlC or Nb4AlC3.
[0025] It is further defined that the ultrasonic treatment time in (b) is 30 min; the centrifugal treatment speed is 3500 rpm and the time is 5 to 10 min.
[0026] It is further defined that the preparation method of the carbon nanotube dispersion is:
[0027] The carbon nanotubes and water are mixed, stirred at 400-700 rpm for 5-10 minutes, and then ultrasonically treated for 15-30 minutes to obtain a carbon nanotube dispersion.
[0028] The second object of the present invention is to provide a Mxene / CNT / metal oxide aerogel encapsulation reinforcement material prepared by the above method.
[0029] The third object of the present invention is to provide an application of the above-mentioned Mxene / CNT / metal oxide aerogel packaging reinforcement material, specifically for radiation-resistant packaging of electronic devices in nuclear power radiation fields, radiation medicine and space radiation environments.
[0030] Beneficial effects:
[0031] The present invention uses MXene as a matrix and carbon nanotubes (CNTs) as a structural reinforcement as a building block for aerogel matrix materials, modifies radiation shielding functional materials on its porous structure and large surface area, uses PVA as a cross-linking agent to improve the mechanical properties of the aerogel, and finally prepares a multifunctional and performance-adjustable MXene / CNT / metal oxide aerogel packaging material through freeze-drying technology. Compared with the prior art, it has at least the following advantages:
[0032] (1) Taking advantage of the fact that the M-position transition metal in the MAX phase of MXene can be Sc, Ti, V, Hf, Ta, and W, the elemental composition can be regulated so that MXene can be a high atomic number material or a low atomic number material. Combined with the two-dimensional layered structure of MXene, the shielding performance can be adjusted, making it a potential shielding material.
[0033] (2) The present invention effectively solves the problem that the traditional functional filler has poor compatibility with the aerogel matrix due to its large volume, which seriously affects the load between the aerogel skeleton, resulting in a decrease in load capacity and affecting performance through the aerogel structural design and filler composition and structure adjustment. The present invention adopts a core-shell structure design and a design that integrates element components into one functional filler to achieve better synergy of multiple elements in the functional filler, better compatibility with the aerogel skeleton, and a larger load capacity (up to 90%), thereby achieving the best radiation shielding performance of the aerogel composite material.
[0034] (3) The present invention makes full use of the lightweight, porous and large surface area characteristics of MXene / CNT aerogels, so that the radiation-resistant functional fillers are fully loaded on the surface of MXene. Compared with polymer-based composite materials, the aerogel skeleton can maximize the loading amount of functional particles and achieve performance improvement, thereby realizing the design and development of lightweight and efficient radiation-resistant packaging reinforcement materials.
[0035] (4) The present invention utilizes the fact that the surfaces of MXene and CNT are negatively charged, while the surfaces of anti-radiation functional filler particles are positively charged, and the functional particles are simply loaded onto MXene through electrostatic self-assembly technology. The loaded particles have good dispersion in the aerogel skeleton, avoiding agglomeration, thereby improving the shielding performance of the anti-radiation packaging reinforcement material.
[0036] (5) The present invention adopts directional freeze-drying technology to achieve directional arrangement of aerogel pores, so that the functional filler is oriented along the pore arrangement, which enhances the probability of interaction with the incident radiation and is beneficial to improving the shielding performance.
[0037] (6) The porous structure of the aerogel prepared by the present invention enables it to have adjustable thickness and density, thereby achieving regulation of the pore structure and then regulation of the shielding performance.
[0038] (7) The aerogel prepared by the present invention also has excellent heat resistance properties, so that it can be used as a packaging material to better protect devices and avoid damage to the devices caused by thermal shock. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The few-layer Ti3C2T in the MXene dispersion prepared in Example 1 x SEM images of
[0040] Figure 2 is the SEM image of carbon nanotubes;
[0041] Figure 3 It is a front view of the aerogel material prepared in Example 2;
[0042] Figure 4A top view of the aerogel material prepared in Example 2;
[0043] Figure 5 This is a SEM photo of the aerogel material prepared in Example 2;
[0044] Figure 6 This is the XRD spectrum of the aerogel material prepared in Example 2. DETAILED DESCRIPTION
[0045] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0046] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0047] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0048] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.
[0049] Example 1
[0050] 1. Ti3C2T x Preparation of MXene dispersion:
[0051] First, 2 g of Ti3AlC2 was etched with 30 mL of 12 M hydrochloric acid and 2 g of lithium fluoride at 35 °C for 30 h, and then centrifuged and washed 6 to 8 times with deionized water until the pH value was close to 7 to obtain a multilayer two-dimensional clay-like structure Ti3C2T x Material.
[0052] Then, the multilayer Ti3C2T xTransfer and ultrasonically treat for 30 minutes in an ice water bath. After the ultrasonic treatment, centrifuge at 3500 rpm for 10 minutes. Collect the upper liquid and continue to add water to the precipitate. Repeat the ultrasonic and centrifugation steps to obtain a MXene dispersion. Then use a pipette to take 3 mL and place it on a suction funnel to filter it into a film. After drying, the film mass is weighed to be 30 mg. The dispersion concentration is determined to be 10 mg / mL, and the microscopic morphology of the film is characterized. The SEM photos are shown in Figure 2. Figure 1 shown.
[0053] 2. Preparation of carbon nanotube dispersion:
[0054] Weigh 0.6g of carbon nanotubes (microscopic SEM photos are shown in Figure 2 The mixture was dispersed in 100 mL of water, stirred at 500 rpm for 10 min, and then ultrasonicated for 30 min to obtain a 6 mg / mL carbon nanotube dispersion.
[0055] 3. Preparation of functional fillers:
[0056] (1) 2.425 g of Bi(NO3)3·5H2O was dissolved in water, 6 g of urea and 1.825 g of CTAB were added, and then the container was transferred to a water bath and reacted at 90°C for 1 h. After the reaction was completed, the solution was cooled to room temperature, washed several times by centrifugation with deionized water, dried, and then heat-treated in air at 600°C for 1 h in a tube furnace, and the powder was collected for later use.
[0057] (2) The powder obtained in the above (1) was dispersed in 80 mL of ethylene glycol, and then 2.9 g of Gd(NO3)3·6H2O was added. The reaction apparatus was transferred to an oil bath at 180°C and stirred for 1.5 h. After cooling to room temperature, the mixture was centrifuged and washed. After drying, the mixture was heat treated at 600°C in air for 1 h to obtain Bi2O3@Gd2O3 powder.
[0058] 4. Aerogel preparation:
[0059] Use a pipette to measure 10 mg / mL Ti3C2T x Dispersion liquid 32mL, take 6mg / mL CNTs dispersion liquid 10.7mL, stir for 5min to make the two fully mixed. Then add 0.768g PVA crosslinker, continue stirring for 10min to make it fully mixed. Weigh 3.456g of the above Bi2O3@Gd2O3 powder, add it to the above mixed solution, and stir it at 600rpm for 2h. After stirring, transfer the mixed solution to a 2×2×2cm mold, place the mold on a copper bridge, immerse one end of the copper bridge in liquid nitrogen at -196℃, and immerse the other end in water at 20℃. Dry it by directional freeze-drying technology to obtain an aerogel material with 90% loading.
[0060] The prepared cubic aerogel material was tested, and its volume was 8cm 3 , mass is 630 mg, density is 0.7875 g / cm 3 , with lightweight characteristics.
[0061] Shielding performance test
[0062] The electron shielding performance of the aerogel material prepared above was tested. The prepared aerogel material with a size of 2×2×2cm was placed in an electron irradiation field with a total accumulated dose of 500krad. The dosimeter was used to calibrate the initial dose and the residual dose after shielding. The calculation results showed that the electron shielding rate of the aerogel material with a size of 2×2×2cm was as high as 81.9%.
[0063] Example 2
[0064] 1. Ti3C2T x Preparation of MXene dispersion:
[0065] First, 4 g of Ti3AlC2 was etched with 40 mL of 40% hydrofluoric acid at room temperature for 24 h, and then centrifuged and washed with deionized water for 6 to 8 times until the pH value was close to 7 to obtain a multilayer accordion-like structure of Ti3C2T x Material.
[0066] Then, multilayer Ti3C2T x 4 g of tetramethylammonium hydroxide (TMAOH) intercalant (any of four general intercalants, including tetramethylammonium hydroxide (TMAOH), tetrabutylammonium hydroxide (TBAOH), dimethyl sulfoxide (DMSO) and ethanol (ET)) was added to the dispersion. After ultrasonic treatment for 30 minutes, centrifugation was performed at 3500 rpm for 10 minutes. After collecting the upper liquid, the precipitate continued to add the intercalant and water and ultrasonic centrifuged. The above steps were repeated to obtain a MXene dispersion. Then 3 mL was taken with a pipette and placed on a suction funnel to filter it into a film. After drying, the membrane mass was weighed to be 24 mg, and the concentration of the dispersion was determined to be 8 mg / mL.
[0067] 2. Preparation of carbon nanotube dispersion:
[0068] 0.4 g of carbon nanotubes were weighed, dispersed in 100 mL of water, stirred at 500 rpm for 10 min, and then ultrasonicated for 30 min to obtain a 4 mg / mL carbon nanotube dispersion.
[0069] 3. Preparation of functional fillers:
[0070] 0.815g Gd2O3 and 3.61g Bi2O3 were dissolved in a small amount of nitric acid and burned with glycine as fuel. The combustion reaction was carried out in a fuel-deficient stoichiometry, where the oxidant to fuel (O / F) ratio was maintained at 1:1.5, and the solution was subsequently dehydrated to a highly viscous liquid (gel), and the temperature was then increased to 250°C, causing the viscous liquid to expand, followed by spontaneous combustion, and a large amount of gas rapidly evolved to produce a large powder. The resulting powder was calcined at 600°C to obtain Bi 1.55 G 0.45 O3 powder.
[0071] 4. Aerogel preparation:
[0072] Use a pipette to measure 8 mg / mL Ti3C2T x Dispersion 40mL, take 16mL of 4mg / mL CNTs dispersion, stir for 5min to mix the two thoroughly. Then add 0.768g PVA crosslinker, continue stirring for 10min to mix thoroughly. Weigh 3.456g Bi 1.55 G 0.45 O3 powder was added to the above dispersion and stirred at 600 rpm for 2 h. After stirring, the dispersion was transferred to a 2×2×2 cm mold, the mold was placed on a copper bridge, one end of the copper bridge was immersed in liquid nitrogen at -196°C, and the other end was immersed in water at 20°C, and dried by directional freeze drying technology to obtain an aerogel material with a loading of 90%.
[0073] The actual picture of the above aerogel material is as follows Figure 3 and Figure 4 As shown by Figure 3 and Figure 4 It can be seen that aerogel materials were successfully prepared through directional freeze-drying technology, and the aerogel materials showed good orientation.
[0074] The microstructure of the aerogel material was characterized, and the SEM photos are shown in Figure 5 As shown by Figure 5 It can be seen that Bi 1.55 G 0.45 The O3 powder is evenly distributed on the aerogel skeleton without agglomeration.
[0075] The XRD spectrum of the above aerogel material is as follows Figure 6 As shown by Figure 6 It can be seen that Bi and Gd form Bi 1.55 G 0.45 O3 material successfully realizes the design of two elements in the same substance.
[0076] The prepared cubic aerogel material was tested, and its volume was 8cm3 , mass is 630 mg, density is 0.7875 g / cm 3 , with lightweight characteristics.
[0077] Shielding performance test
[0078] The electron shielding performance of the aerogel material prepared in the embodiment was tested. The prepared aerogel material with a size of 2×2×2 cm was placed in an electron irradiation field with a total cumulative dose of 500 krad. A dosimeter was used to calibrate the initial dose and the remaining dose after shielding. The calculation results showed that the electron shielding rate of the aerogel material with a size of 2×2×2 cm was as high as 80.5%.
[0079] Comparative Example 1
[0080] The difference between this comparative example and the embodiment is that step 3 is not performed, and the mixture of Bi2O3 powder and Gd2O3 powder is directly used as the functional filler. The remaining process steps and parameter settings are the same as those in embodiment 1.
[0081] The specific operation process is as follows:
[0082] 1. Ti3C2T x Preparation of MXene dispersion:
[0083] First, 4 g of Ti3AlC2 was etched at 35 °C for 30 h using a mixture of 30 mL of 12 M hydrochloric acid and 4 g of lithium fluoride, and then centrifuged and washed 6 to 8 times with deionized water until the pH value was close to 7 to obtain a multilayer two-dimensional clay-like structure Ti3C2T x Material.
[0084] Then, the multilayer Ti3C2T x Transfer and ultrasonically treat for 30 minutes in an ice water bath. After the ultrasonic treatment, centrifuge at 3500 rpm for 10 minutes. Collect the upper liquid and continue to add water to the precipitate. Repeat the ultrasonic and centrifugation steps to obtain a MXene dispersion. Then use a pipette to take 3 mL and place it on a suction funnel to filter it into a film. After drying, the film mass is weighed to be 30 mg. The dispersion concentration is determined to be 10 mg / mL, and the microscopic morphology of the film is characterized. The SEM photos are shown in Figure 2. Figure 1 shown.
[0085] 2. Preparation of carbon nanotube dispersion:
[0086] Weigh 0.6g of carbon nanotubes (microscopic SEM photos are shown in Figure 2 The mixture was dispersed in 100 mL of water, stirred at 500 rpm for 10 min, and then ultrasonicated for 30 min to obtain a 6 mg / mL carbon nanotube dispersion.
[0087] 3. Aerogel preparation:
[0088] Use a pipette to measure 10 mg / mL Ti3C2T x Dispersion liquid 32mL, take 6mg / mL CNTs dispersion liquid 10.7mL, stir for 5min to make the two fully mixed. Then add 0.768g PVA crosslinker, continue stirring for 10min to make it fully mixed. Weigh 1.728g Bi2O3 powder and 1.728g Gd2O3 powder, add to the above mixture, and stir at 600rpm for 2h. After stirring, transfer the mixture to a 2×2×2cm mold, place the mold on a copper bridge, immerse one end of the copper bridge in liquid nitrogen at -196℃, and immerse the other end in water at 20℃, and dry it by directional freeze-drying technology to obtain an aerogel material with 90% loading.
[0089] The electron shielding performance of the aerogel material prepared in the example was tested. The prepared aerogel material with a size of 2×2×2 cm was placed in an electron irradiation field with a total cumulative dose of 500 krad. The initial dose and the remaining dose after shielding were calibrated using a dosimeter. The calculation results showed that the electron shielding rate of the aerogel material with a size of 2×2×2 cm was 69%, which was lower than 81.9% of Example 1. This is because although 90% of the loading amount of the functional filler was achieved in Comparative Example 1, obvious agglomeration occurred, affecting its shielding performance.
[0090] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a Mxene / CNT / metal oxide aerogel encapsulation reinforcement material, characterized in that: After the MXene dispersion and the carbon nanotube dispersion are evenly mixed, PVA is added, and after continuing to stir and mix thoroughly, a functional filler is added, and continuing to stir evenly to obtain a slurry; then the slurry is placed in a mold and dried using a freezing technique to obtain a MXene / CNT / metal oxide aerogel encapsulation material; The functional filler is Bi2O3@Gd2O3 powder or Bi x G 2-x O3 powder.
2. The preparation method according to claim 1, characterized in that: The MAX phase of the MXene dispersion is Ti3AlC2, Ti2AlC, Ta4AlC3, Ta2AlC, Nb2AlC or Nb4AlC3, with a concentration of 5 to 15 mg / mL; the concentration of the carbon nanotube dispersion is 5 to 15 mg / mL.
3. The preparation method according to claim 1, characterized in that: The mass ratio of Mxene to carbon nanotubes in the slurry is 3-6:1; the mass ratio of PVA to the total mass of Mxene and carbon nanotubes is 1-3:1; and the mass of the functional filler is 1-90% of the total mass of Mxene and carbon nanotubes.
4. The preparation method according to claim 1, characterized in that: The preparation method of Bi2O3@Gd2O3 powder with core-shell structure includes: (1) Bi(NO3)3·5H2O, a precipitant, CTAB and water are mixed and reacted in a water bath at 90°C for 1 hour. The obtained precipitate is washed with deionized water, dried, and then placed in a tube furnace in an air atmosphere at 300-600°C for heat treatment for 1-2 hours. The powder is collected for later use; (2) The powder obtained in step (1), Gd(NO3)3·6H2O and ethylene glycol are mixed, stirred at 180°C for 1-1.5 h, naturally cooled to room temperature and rinsed, and the powder obtained after drying is heat treated at 600°C for 1-2 h to obtain Bi2O3@Gd2O3 powder with a core-shell structure.
5. The preparation method according to claim 4, characterized in that: The mass ratio of Bi(NO3)3·5H2O and Gd(NO3)3·6H2O is (0~1):
1.
6. The preparation method according to claim 4, characterized in that: The precipitant is urea or ammonia.
7. The preparation method according to claim 1, characterized in that: Bi x G 2-x The preparation method of O3 powder is as follows: using glycine as fuel, Gd2O3 and Bi2O3 are dissolved in nitric acid to obtain a slurry, and then the slurry is dehydrated into a gel, and the temperature is raised to 250°C, and the gel is spontaneously combusted to obtain a combustion powder; then the combustion powder is calcined at 600°C for 1 to 3 hours to obtain Bi x G 2-x O3 powder.
8. The preparation method according to claim 7, characterized in that: The O / F ratio during the combustion process was 1:1.
5.
9. A Mxene / CNT / metal oxide aerogel encapsulation reinforcement material prepared by the method according to any one of claims 1 to 8.
10. An application of the Mxene / CNT / metal oxide aerogel encapsulation reinforcement material according to claim 9, characterized in that: Used for radiation-resistant packaging of electronic devices in nuclear power radiation fields, radiation medicine and space radiation environments.
Citation Information
Patent Citations
Preparation method of MXene-CNT / carbon aerogel composite material
CN113645820A
Rare earth oxide nano-particle doped Mxene material for space charged particle radiation protection, composite coating and preparation method
CN113956846A
MXene / CNT and oxidized sodium alginate modified collagen composite aerogel as well as preparation method and application thereof
CN116589742A
Preparation method of MXene / rGO / CNT composite electromagnetic shielding material with three-dimensional hollow structure
CN117794214A
MXene-based aerogel, preparation method thereof and application of MXene-based aerogel in wave-absorbing material
CN117939870A